Neural mechanisms of attending to items in working memory. (June 2019) - Manohar, Sanjay G.; Zokaei, Nahid; Fallon, Sean J.; Vogels, Tim P.; Husain, Masud
Highlights: Evidence suggests both sustained activity and synaptic plasticity support working memory. Rapid Hebbian plasticity can support flexible attractor states analogous to a focus of attention. Plastic attractors can account for dynamic neural shifts in memory representations. Abstract: Working memory, the ability to keep recently accessed information available for immediate manipulation, has been proposed to rely on two mechanisms that appear difficult to reconcile: self-sustained neural firing, or the opposite—activity-silent synaptic traces. Here we review and contrast models of these two mechanisms, and then show that both phenomena can co-exist within a unified system in which neurons hold information in both activity and synapses. Rapid plasticity in flexibly-coding neurons allows features to be bound together into objects, with an important emergent property being the focus of attention. One memory item is held by persistent activity in an attended or "focused" state, and is thus remembered better than other items. Other, previously attended items can remain in memory but in the background, encoded in activity-silent synaptic traces. This dual functional architecture provides a unified common mechanism accounting for a diversity of perplexing attention and memory effects that have been hitherto difficult to explain in a single theoretical framework.